anonymous
  • anonymous
Solve the following system of equations. 2x – 3y + z = –1 2x – 2y – 2z = –8 x + 5y – 3z = 2
Mathematics
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions.

anonymous
  • anonymous
Solve the following system of equations. 2x – 3y + z = –1 2x – 2y – 2z = –8 x + 5y – 3z = 2
Mathematics
katieb
  • katieb
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
ok lets do this
anonymous
  • anonymous
first of all we want to eliminate a value
anonymous
  • anonymous
so you choose 2 of the equations and eliminate z

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
(2x-3y+z)2 2x-2y-2z
anonymous
  • anonymous
4x-6y+2z 2x-2y-2z
anonymous
  • anonymous
Okay, and then what do you do?
anonymous
  • anonymous
sec i gorgot the consonate
anonymous
  • anonymous
4x-6y+2x=-2 2x-2y-2z= -8
anonymous
  • anonymous
6x-8y=-10
anonymous
  • anonymous
2x – 3y + z = –1 2x – 2y – 2z = –8 x + 5y – 3z = 2
anonymous
  • anonymous
so now you take the equation we didnt use and eliminate z
anonymous
  • anonymous
x+5y-3z = 2 (2x-3y+z=-1)3
anonymous
  • anonymous
x+5y-3z=2 6x-9y+3z=-3
anonymous
  • anonymous
7x-4y=-3
anonymous
  • anonymous
7x-4y=-3 6x-8y=-10
anonymous
  • anonymous
any questions so far?
anonymous
  • anonymous
those are the 2 values we get after eliminating the z from equations
anonymous
  • anonymous
so we can solve for x and y now
anonymous
  • anonymous
(7x-4y=-3)2 6x-8y=-10
anonymous
  • anonymous
-2 oops
anonymous
  • anonymous
thank you soo much! i think i understand this a lot better now
anonymous
  • anonymous
-14x+8y=6 6x-8y=-10
anonymous
  • anonymous
-8x=-16
anonymous
  • anonymous
x=2
anonymous
  • anonymous
(7x-4y=-3)6 (6x-8y=-10)-7
anonymous
  • anonymous
42x-24y=-18 -42x+56y=-70
anonymous
  • anonymous
opps that +70
anonymous
  • anonymous
32y=52
anonymous
  • anonymous
y=52/32
anonymous
  • anonymous
y=13/8
anonymous
  • anonymous
so lets check our y value
anonymous
  • anonymous
6x-8y=-10
anonymous
  • anonymous
plug in x
anonymous
  • anonymous
6(2)-8y=-10

Looking for something else?

Not the answer you are looking for? Search for more explanations.